2018
DOI: 10.1590/0102-311x00206716
|View full text |Cite
|
Sign up to set email alerts
|

Adequação normativa dos planos estaduais de segurança alimentar e nutricional no Brasil

Abstract: Resumo Com o intuito de analisar a adequação dos Planos Estaduais de Segurança

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 25 publications
(29 reference statements)
0
26
0
4
Order By: Relevance
“…In the last 15 years, several studies have been identified in the field of public policies on food and nutrition in Brazil, some of which have addressed the issue in a comprehensive way [4][5][6], while others have focused on the analysis of specific programs, such as the Programa Nacional de Alimentação Escolar (PNAE, National School Nutrition Program) [7][8][9][10]; the Programa Bolsa Família (PBF, Family Grant Program) [11][12][13][14]; the Programa de Aquisição de Alimentos (PAA, Food Acquisition Program) [15,16]; the government-backed economy restaurants program [17,18]; and the Sistema Nacional de Segurança Alimentar e Nutricional (SISAN, National System of Food and Nutrition Security) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, several studies have been identified in the field of public policies on food and nutrition in Brazil, some of which have addressed the issue in a comprehensive way [4][5][6], while others have focused on the analysis of specific programs, such as the Programa Nacional de Alimentação Escolar (PNAE, National School Nutrition Program) [7][8][9][10]; the Programa Bolsa Família (PBF, Family Grant Program) [11][12][13][14]; the Programa de Aquisição de Alimentos (PAA, Food Acquisition Program) [15,16]; the government-backed economy restaurants program [17,18]; and the Sistema Nacional de Segurança Alimentar e Nutricional (SISAN, National System of Food and Nutrition Security) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The multidimensionality of the concept of Food and Nutrition Security adopted by Brazil imposes challenges for the implementation of an inherently intersectoral public policy. In addition, it exposes the necessity to think of evaluative strategies that can respond by their amplitude, through indicators and by methodologies and instruments of comprehensive and systemic information collection [1].…”
Section: Introductionmentioning
confidence: 99%
“…Although all states have, since 2014, already been members of the National System of Food and Nutrition Security, at the time of this survey only Santa Catarina, Bahia and Paraíba had a plan in action [1]. Of these, the Plan of Santa Catarina (State of Santa Catarina Food and Nutrition Security Plans), published in 2014 and valid until 2019, was the best evaluated in relation to the normative aspects [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From then on, states and cities have been encouraged to implement this Public Policy in their territories, and by 2014 all Brazilian states had already signed up to SISAN [4]. At the three levels of government, the FNS Plans are the main planning, management and implementation tools of the PNSAN [2].…”
Section: Introductionmentioning
confidence: 99%